Fractional order PD controller design for non-monotonic phase systems - Goud K.M.; Nagar S.K. (My University, 2025)
This paper presents a novel technique for the analytical design of the fractional order controller for non-monotonic phase systems. The PD controller is designed for non-monotonic system based on gain crossover frequency and phase margin specifications. The method provides a minimum phase margin in the desired bandwidth. The proposed method redefines the concept of phase margin for non-monotonic system with decreasing phase. Introduction of the fractional power parameters offers some advantage in terms of robust performance. For comparison, the proposed non-monotonic method and the conventional method are chosen for the same set of tuning constraints. Copyright © 2015 Inderscience Enterprises Ltd.